Taxation on Sugar-Sweetened Beverages Across the European Union Member States - Nikolova, Velichka (Research Papers, 2025)
The present study examines an issue that has recently been the subject of numerous discussions in the field of the tax system, specifically the taxation on sugar-sweetened beverages. The topic is extremely relevant in view of the possibility that through this type of tax legislation. countries may try to counteract the spread of some of the most significant diseases facing humanity. For this purpose, the need for the introduction of taxation on sugar-sweetened beverages is argued, the expected effects of the application of the fiscal instrument are emphasized, and the specifics of the taxation of the analyzed products within the European Union countries are also traced.
Keywords: Taxation; Sugar-sweetened beverages; European union